2010
DOI: 10.1017/s0047279410000693
|View full text |Cite
|
Sign up to set email alerts
|

Using Identity and Recognition as a Framework to Understand and Promote the Resilience of Caregiving Children in Western Kenya

Abstract: Children around the world have been observed to assume caregiving responsibilities when a parent or other family members fall ill. Whilst the circumstances surrounding caregiving children in Anglophone countries have been looked at in detail, we know relatively little about how children in Africa experience young caregiving. This paper seeks to further our understanding of caregiving children in Africa by looking at how local constructions of childhood can facilitate their agency and resilience, paying particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 63 publications
1
50
1
Order By: Relevance
“…The paper argues that there is a need to create opportunities for young carers in Britain to encounter different and new ways of seeing young caregiving, allowing some to develop more positive carer identities. Drawing on previous findings (Skovdal & Andreouli, 2011), we argue that such positive identities build children's self-esteem amd enhance their resilience and ability to deal with hardship.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…The paper argues that there is a need to create opportunities for young carers in Britain to encounter different and new ways of seeing young caregiving, allowing some to develop more positive carer identities. Drawing on previous findings (Skovdal & Andreouli, 2011), we argue that such positive identities build children's self-esteem amd enhance their resilience and ability to deal with hardship.…”
Section: Introductionmentioning
confidence: 52%
“…This provides caregiving children and youth in sub-Saharan Africa with a different set of resources they can draw on to make sense of their circumstances. In Kenya for example, we found that young carers were respected by local community members and received recognition for their efforts (Skovdal and Andreouli 2011). This recognition enabled the children and youth to construct positive social identities that facilitate resilience and give meaning to very difficult circumstances.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…give positive meanings to difficult circumstances (Robson and Ansell 2000;Robson, Ansell et al 2006;Evans and Becker 2009;Skovdal and Andreouli 2011).…”
Section: Young Caregivingmentioning
confidence: 99%
“…First, community members can provide development workers with a wealth of information that is expressive of local realities, social dynamics and responses to hardship (Campbell and Jovchelovitch 2000). Local knowledge may for example reveal the practical and symbolic resources that communities can contribute to the provision of services (Skovdal and Andreouli 2010;Skovdal and Campbell 2010). Second, bringing forward local recommendations is necessary if we are to move beyond a recognition of what outsiders can and need to do to support young carers and come to an agreement -between global and local actors -on how best to work together to provide young carers with meaningful support (Jovchelovitch 2007).…”
Section: Malementioning
confidence: 99%